Exploring the physical attributes of elite épée fencing: a Delphi study of world-class coaches - Cree, J. A.; Newman, H. J.; Norris, L. A.; Oates, L. W.; Turner, A. N. (The Journal of Sports Medicine and Physical Fitness, 2026)
BACKGROUND: This study aimed to identify and rank the physical attributes deemed most important for elite performance in épée fencing, from the perspective of world-class coaches. While extensive biomechanical and physiological research exists in fencing, limited attention has been paid to the experiential insights of elite coaches.